Radiocarbon Dates on Some Quaternary Mammals and Artifacts from Northern North America - Harington, C.R. (ARCTIC, 1980)
Nine radiocarbon dates on five genera of Quaternary mammals from northern North America are discussed. Of particular interest are: (a) a 29,000-year-old artifact from the Yukon Territory; (b) the first evidence that steppe mammoths (Mammathus columbi or M. armeniacus) occupied eastern Beringia during the peak of the Wisconsin glaciation; (c) dates indicating that saiga antelopes (Saiga tatarica) and Yukon short-faced bears (Arctodus simus yukonensis) occupied the Yukon-Alaska region in mid-Wisconsin time; (d) dates indicating that bison (Bison sp.) lived near the arctic coast of the Northwest Territories, and tundra muskoxen (Ovibos moschatus) lived in the western Yukon in late postglacial time; and (e) dates suggesting that tundra muskoxen have occupied the central Canadian Arctic Islands for the last 7000 years.